MENINGKATKAN EFEKTIVITAS PENCATATAN KEUANGAN MELALUI MEDERNISASI SISTEM INFORMASI AKUNTANSI - Januar Batista Ardana; Fathor Rohman; Roni Yanto (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to compare compilers and interpreters in programming, focusing on their advantages, disadvantages, and optimal usage contexts. The primary difference between a compiler and an interpreter lies in their execution methods and speed,   where a compiler translates the entire source code into machine language before execution, while an interpreter translates the code line by line during runtime. The research method employed is a literature review, analyzing various journals, books, and relevant online sources from the last five years. The findings indicate that compilers excel in execution speed and long-term program efficiency, whereas interpreters offer greater flexibility for testing, debugging, and developing applications that require rapid changes. In conclusion, the choice between a compiler and an interpreter depends on the project’s requirements, available resources, and the objectives of software development.